Cardiolipin Synthesis in Brown and Beige Fat Mitochondria Is Essential for Systemic Energy Homeostasis - Sustarsic, Elahu G; Ma, Tao; Lynes, Matthew D; Larsen, Michael; Karavaeva, Iuliia; Havelund, Jesper F; Nielsen, Carsten H; Jedrychowski, Mark P; Moreno-Torres, Marta; Lundh, Morten; Plucinska, Kaja; Jespersen, Naja Z; et al. (Cell metabolism, 2018)
Activation of energy expenditure in thermogenic fat is a promising strategy to improve metabolic health, yet the dynamic processes that evoke this response are poorly understood. Here we show that synthesis of the mitochondrial phospholipid cardiolipin is indispensable for stimulating and sustaining thermogenic fat function. Cardiolipin biosynthesis is robustly induced in brown and beige adipose upon cold exposure. Mimicking this response through overexpression of cardiolipin synthase (Crls1) enhances energy consumption in mouse and human adipocytes. Crls1 deficiency in thermogenic adipocytes diminishes inducible mitochondrial uncoupling and elicits a nuclear transcriptional response through endoplasmic reticulum stress-mediated retrograde communication. Cardiolipin depletion in brown and beige fat abolishes adipose thermogenesis and glucose uptake, which renders animals insulin resistant. We further identify a rare human CRLS1 variant associated with insulin resistance and show that adipose CRLS1 levels positively correlate with insulin sensitivity. Thus, adipose cardiolipin has a powerful impact on organismal energy homeostasis through thermogenic fat bioenergetics.